STUDI EMPIRIS KINERJA KEUANGAN SEBELUM DAN SESUDAH AKUISISI PADA PT. BTPN SYARIAH TBK DI INDONESIA - Supeni, Retno Endah; Ruspita, Rayna Rika (Jurnal Ilmiah Akuntansi Indonesia, 2019)
Abstract:The empirical study analyzed and tested the significant differences in the financial performance of PT BTPN Syariah Tbk in Indonesia, two years before (2012-2013) and five years (2014-2018) after the acquisition. Financial performance assessment uses the RGEC method (Risk Profile, Good Corporate Governance, Earning, and Capital) by collecting company financial statement data related to research variables and ranking each NPF Gross analysis, NPF Net, FDR, GCG, ROA, ROE, NOM , BOPO and KPMM by assessing the soundness of the bank and conducting a Paired Sample T test. The results show a test of statistical differences in financial ratios of Bank PT. BTPN Syariah Tbk before and after the acquisition of the NPF Gross variable; NPF Net; FDR; ROA; BOPO there are significant differences and ROE variables; NOM; There is no significant difference in KPMM while the manual analysis of the research variables, before and after the acquisition shows the better position of NPF Net; ROA, ROE, NOM, KPMM, CGS remains good and FDR, NPF Gross, BOPO gets worse. The research implications are used to determine the effectiveness of acquisition policies, strategic planning information to prepare for acquisitions in order to form a better BUS than the previous banks which were first BUS and evaluation of decisions related to the obligation to change UUS to BUS in 2023.Keywords: Acquisition, Financial Performance